Sagot :
let 'x' be the factor such that it can be expressed as 4x:7x
Since the difference is 48 then you'll have it as
7x - 4x = 48
3x = 48
x = 16
4x = 4(16)
= 64
7x = 7(16)
= 112
Getting the sum you'll have:
Sum = 64 + 112
= 176
Since the difference is 48 then you'll have it as
7x - 4x = 48
3x = 48
x = 16
4x = 4(16)
= 64
7x = 7(16)
= 112
Getting the sum you'll have:
Sum = 64 + 112
= 176
4:7 can be written as 4x:7x
4x-7x=48
-3x=48
x=-16
Substitute but this time its addition
4x+7x=y
4(-16)+7(-16)=y
-64-112=y
y=-176
4x-7x=48
-3x=48
x=-16
Substitute but this time its addition
4x+7x=y
4(-16)+7(-16)=y
-64-112=y
y=-176